Landscape changes in the grapes of Putnok town - Oszkocsil, Zoltán (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
Historical processes and landscape changes of the grapes / grape yards around Putnok town (situated at the edge of the Putnok Hills and the Sajó Valley geographical micro-regions) are presented. These analyses are based on historical maps, field studies, and narrations of local inhabitants. Knowing the historical development of grape production in the Carpathian Basin I state that, although the first written documents of grape production around Putnok town date back to the 13th century, it is almost sure that the formation and generation of grape yards had already started in the 10th century, by opening the close forests. These grape yards played a very important role in the life of the town and its surroundings. Their decline has been constant since the vine-pest epidemic. I present the landscape changes that are tied to the grape production through a row of historical maps. These processes resulted in the occurrence of nature protected plant species. It has become obvious that not all the areas were cultivated, or for not that long time, as the maps show. Weed infestation, and sometimes the expansion of invasive alien species, is significant in those parcels that have been abandoned during the past 20 years. The regeneration of (semi-) natural grasslands and closure of the grass surface are slow, but still constant processes in the parcels that have been abandoned long time ago, and resulted in the appearance of the following protected plant species: Orchis morio, Linum tenuifolium, Diantus collinus, Pulsatilla pratensis subsp. nigricans, P. p. subsp. zimmermannii, P. grandis, Polygala major, Echium maculatum, Iris variegata.